Innovation and Financial Inclusion: A review of the literature - Yawe, Bruno L.; Prabhu, Jaideep (Journal of Payments Strategy & Systems, 2015)
Financial innovation is a major driver of financial inclusion, and its relationship with inequalities in income and opportunities raises some important policy questions. This review covers the following areas of financial inclusion: savings; microinsurance; payments; banking services for the excluded poor; financial literacy; and consumer protection. The review shows that increasing financial inclusion should go beyond the traditional banking sector. This is because mobile network operators have, in most cases, initiated mobile money services, although this is not within the mandate for which they were initially licensed. This has aided the provision of financial services to the majority without bank accounts. There is now competition between commercial banks and mobile network operators, especially when the latter expand financial products on their networks. Partnerships should be established between and among commercial banks as well as between mobile network operators providing mobile money services to fast track interoperability. In most cases, the appropriate institutional and regulatory framework was absent at the inception of mobile money services. Therefore, there is a need for an institutional framework composed of regulators of telecommunications; for mobile network operators as well as central banks to expand financial inclusion without compromising the strategies aimed at eliminating contemporary global challenges such as money laundering.
Keywords: Big data; Mobile money; Digital currency; Financial inclusion; Financial innovation